The Role Of Auguste Comte's Philosophy In The Evolution Of Knowledge: An Analysis Of Philosophical Perspectives On The Classification Of Science - Suratno Suratno; Fairuz Maharani Deasiyanti; Tsamara Ghinah Salsabilah Wiajaya; I Ketut Mahardika (Jurnal Ilmiah Wahana Pendidikan, 2023)
This comprehensive qualitative literature study examines the profound impact of Auguste Comte's philosophy on the evolution of knowledge, specifically focusing on the analysis of philosophical perspectives regarding the classification of science. Through a systematic and critical analysis of diverse and reputable sources, this study explores Comte's thoughts and ideas, employing a philosophical approach to understand the influence of his philosophy on the organization and development of scientific knowledge. The findings highlight the hierarchical classification of science proposed by Comte, emphasizing the interdependence of scientific disciplines and the role of philosophy in synthesizing knowledge. The study contributes to our understanding of Comte's contributions and their implications for the evolution of knowledge